Latar Belakang dan Bentuk-Bentuk Diskriminasi Pada Cerpen Dūmah Wad Ḥāmid Karya Ṭayyib Ṣāliḥ - Ghazali, Muhammad Irvan; Ferawati, Ferawati; Khasanah, Nisrina Noor (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2024)
This research aims to find out the factors of discrimination and the forms of discrimination experienced by the people of Wad Ḥāmid village as well as the resistance carried out by the people of Wad Ḥāmid village in the short story Dūmah Wad Ḥāmid. The method used in this research is a descriptive qualitative method with data collection techniques in the form of reading and recording techniques. The data analysis technique is done by describing the discrimination data based on Newman's discrimination theory. The results in this study include; (1) There are 3 factors behind the discrimination experienced by the people of Wad Ḥāmid village in the short story Dūmah Wad Ḥāmid, namely, environmental influence factors in the form of an environment filled with flies, infrastructure underdevelopment factors in the form of inadequate transportation, no health facilities, no electricity, no interesting places to visit, and stagnant village development and physical differences in the form of thicker skin than humans in general. (2) There are 3 forms of discrimination experienced by the people of Wad Ḥāmid village in the short story Dūmah Wad Ḥāmid, namely, verbal discrimination, avoidance discrimination, and expense discrimination.